2010
DOI: 10.1371/journal.pone.0008671
|View full text |Cite
|
Sign up to set email alerts
|

The p38 MAPK Regulates IL-24 Expression by Stabilization of the 3′ UTR of IL-24 mRNA

Abstract: BackgroundIL-24 (melanoma differentiation-associated gene-7 (mda-7)), a member of the IL-10 cytokine family, possesses the properties of a classical cytokine as well as tumor suppressor effects. The exact role of IL-24 in the immune system has not been defined but studies have indicated a role for IL-24 in inflammatory conditions such as psoriasis. The tumor suppressor effects of IL-24 include inhibition of angiogenesis, sensitization to chemotherapy, and p38 mitogen-activated protein kinase (MAPK)-mediated ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 44 publications
2
28
0
1
Order By: Relevance
“…These results extend observations on stimulation of IL-20 upon hypoxia (Chen and Chang, 2009) and UVB irradiation (Hunt, et al, 2006). Both IL-20 and IL-24 expression is dependent on p38 MAPK (Otkjaer, et al 2010;Otkjaer, et al, 2007), which is increased in KS cells (own unpublished results). This cytokine has been shown to specifically inhibit the activation of NF-kappaB induced by interleukin 1 family, member 6 (Blumberg, et al, 2007), but its contribution to KS phenotypes remains to be established.…”
Section: Inflammation and Dermal Fibrosis In Ks Skin In Vivosupporting
confidence: 85%
See 1 more Smart Citation
“…These results extend observations on stimulation of IL-20 upon hypoxia (Chen and Chang, 2009) and UVB irradiation (Hunt, et al, 2006). Both IL-20 and IL-24 expression is dependent on p38 MAPK (Otkjaer, et al 2010;Otkjaer, et al, 2007), which is increased in KS cells (own unpublished results). This cytokine has been shown to specifically inhibit the activation of NF-kappaB induced by interleukin 1 family, member 6 (Blumberg, et al, 2007), but its contribution to KS phenotypes remains to be established.…”
Section: Inflammation and Dermal Fibrosis In Ks Skin In Vivosupporting
confidence: 85%
“…Thus far, little has been known about the functions of these cytokines in the skin. A recent study reported their induction after skin injury (Roupe, et al, 2010), and previous investigations suggested regulation of these interleukins through stress induced pathways (Chen and Chang, 2009;Hunt, et al, 2006;Otkjaer, et al, 2010;Otkjaer, et al, 2007). To corroborate this in KS, we used three different well-established methods -hypoxia, oxidative stress and UVB irradiation -to induce cell stress in normal and KS keratinocytes and showed that stress enhances expression and secretion of IL-20 and IL-24 by KS cells.…”
Section: Inflammation and Dermal Fibrosis In Ks Skin In Vivomentioning
confidence: 74%
“…Reverse transcription and quantitative PCR were carried out essentially as described earlier (35). TaqMan probes (Applied Biosystems, assay-IDs as follows: NFKBIA, Hs00153283_m1; NFKBID, Hs00262018_m1; IL-6, Hs00174131_m1; GAPDH, Hs99999905_m1; IL-8, Hs00174103_m1) were used with TaqMan Fast Universal PCR Master Mix (2ϫ) (Applied Biosystems).…”
Section: In Vitro Transcription and Electrophoretic Mobility Shift Asmentioning
confidence: 99%
“…This may be because the hairpin structure of pri-miRNA and its insertion changed the secondary structure of 3′UTR of GFP gene. Some studies confirmed that 3′UTR can affect the gene expression (Mazumder et al, 2005;Otkjaer et al, 2010;Wang et al, 2006;Zearfoss et al, 2011). In mouse, miR-1 and miR-133 are clustered together on the same chromosomal loci, where they are separated by 9.3 kb, and transcribed together in a tissue-specific manner during development .…”
Section: Discussionmentioning
confidence: 91%